Pearl Oyster Bacterial Community Structure Is Governed by Location and Tissue-Type, but Vibrio Species Are Shared Among Oyster Tissues - King, William L.; Kaestli, Mirjam; Siboni, Nachshon; Padovan, Anna; Christian, Keith; Mills, David; Seymour, Justin; Gibb, Karen (Frontiers in Microbiology, 2021)
Diseases of bivalves of aquacultural importance, including the valuable Australian silver-lipped pearl oyster (Pinctada maxima), have been increasing in frequency and severity. The bivalve microbiome is linked to health and disease dynamics, particularly in oysters, with putative pathogens within the Vibrio genus commonly implicated in oyster diseases. Previous studies have been biased towards the Pacific oyster because of its global dominance in oyster aquaculture, while much less is known about the microbiome of P. maxima. We sought to address this knowledge gap by characterising the P. maxima bacterial community , and we hypothesised that bacterial community composition, and specifically the occurrence of Vibrio, will vary according to the sampled microenvironment. We also predicted that the inside shell swab bacterial composition could represent a source of microbial spillover biofilm into the solid pearl oyster tissues, thus providing a useful predictive sampling environment. We found that there was significant heterogeneity in bacterial composition between different pearl oyster tissues, which is consistent with patterns reported in other bivalve species and supports the hypothesis that each tissue type represents a unique microenvironment for bacterial colonization. We suggest that, based on the strong effect of tissue-type on the pearl oyster bacterial community, future studies should apply caution when attempting to compare microbial patterns from different locations, and when searching for disease agents. The lack of association with water at each farm also supported the unique nature of the microbial communities in oyster tissues. In contrast to the whole bacterial community , there was no significant difference in the Vibrio community among tissue types nor location. These results suggest that Vibrio species are shared among different pearl oyster tissues. In particular, the similarity between the haemolymph, inside shell and solid tissues, suggests that the haemolymph and inside shell environment is a source of microbial spillover into the oyster tissues, and a potentially useful tool for non-destructive routine disease testing and early-warning surveillance. These data provide important foundational information for future studies identifying the factors that drive microbial assembly in a valuable aquaculture species.